أثر السياسة المحاسبية العدوانية على تكلفة رأس المال المملوك للشركات السورية المساهمة المسجلة في هيئة الأوراق والأسواق المالية السورية - ريا فاتن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى التحقق من وجود علاقة ما بين السياسة المحاسبية العدوانية للشركات وتكلفة رأس مالها المملوك، منطلقاً في ذلك من دراسات سابقة أشارت إلى أن السياسات المحاسبية للشركات تعد من القنوات المرسلة للإشارة التي ترشد المستثمرين في قراراتهم الاستثمارية. لتحقيق هذا الهدف تم إجراء مسح على الشركات السورية المساهمة المسجلة في هيئة الأوراق والأسواق المالية السورية باستخدام البيانات الثانوية في إطار دراسة اتجاهية تمتد من 2009 إلى 2014. أظهرت نتائج هذا البحث عدم وجود علاقة ما بين السياسة المحاسبية العدوانية وتكلفة رأس المال المملوك للشركات السورية المساهمة، وهذا ما خالف النتائج التي توصلت إليها الدراسات السابقة والذي يعود سببه إلى عدم أخذ متغيرات أخرى بعين الاعتبار تتفاعل مع السياسات العدوانية أثناء تأثيرها على تكلفة رأس المال المملوك. This research aims to verify the existence of a relationship between the aggressive accounting policy of corporations and its cost of equity capital. This study starts from number of previous studies which have indicated that the accounting policies of corporations are just signal transmitted channels which guide investors in their decisions. To achieve this goal, a survey study has been conducted on the Syrian registered corporations in the Syrian commission on financial markets and securities using secondary data with quasi-experimental design for the period from 2009 to 2014. The results of this research showed that there is no relation between aggressive accounting policy and the cost of equity capital of the Syrian registered corporations in the Syrian commission on financial markets and securities, and this result violates the results of previous studies which may be due to not taking other variables in mind which interact with the aggressive policies while it affects the cost of equity capital.